Performance of Mortar Incorporating Heat-Treated Drinking Water Treatment Sludge as a Silica-Sand Replacement - Mohammad Al-Rawashdeh; Ahmed Alzoubi; Shadi Hanandeh; Isam Yousef; Mohammad Al-Nawaiseh (Salehan Institute of Higher Education, 2022)
This paper examines the possibility of using water purification wastes in the production of mortar. Within the study context, XRD and XRF analyses were performed to obtain the chemical composition of sludge. Moreover, heat-treated sludge at a temperature of 900ºC was used in the preparation of mortar mixes as a partial sand replacement (5, 10, 15, and 20% by sand weight) with a w/c of 0.48. Fresh mortars were tested for workability, and mortar samples with 7, 28, and 90 days curing ages were tested for dry density, absorption, ultrasonic pulse velocity (UPV), and compressive and flexural strengths. Besides, some regression modeling was conducted for each of the measured parameters. In general, the results showed that the use of up to 10% incinerated sludge by sand weight leads to a slight decrease in the workability and density of the mixture and a 10% increase in its strength. Nevertheless, mortars with sludge content of over 10% showed a significant increase in water absorption and a decrease in strength and other properties. Doi: 10.28991/CEJ-2022-08-08-08 Full Text: PDF